Development of UiTM e-Rental application / Norshakila Baharuddin - Baharuddin, Norshakila (2006)
Students have a difficulty to find the suitable rental house that match with their needs because of the limited information provided in rental house advertisements through mass-media and mass-electronic. It is difficult for them to visualize the house without any additional details information. Some of the house owner and landlord also give false information about the actual condition of the house to the students. The worst thing is when the students signs a lease or agreement without previously viewing the property and only realize the truth after they had rent that house. The objectives of this research are to to identify student's requirements during finding the rental house and to develop a web based application prototype for rental house selection in Shah Alam. A successful research is determined from the proper planning. The time allocation is done before one can begin the project. In order to gather the information for this project, the techniques that had been used are conduct interview, survey and research. The system design divides to two phases which is testing and troubleshooting. The report writing will be finalized after the project findings and recommendation has been concluded. With this web-based system, the output that needed can be gathered faster and effectively. Student also can get the details information about the rental house selected at anywhere and any time they want. This web-based system is hopefully can assist student in finding rental house that meets their requirement at the minimum cost and time. In the future, due to the advantage and problem arise, the system can be improved by extend the scope of the system in order to make the system more effectively.